1999
DOI: 10.1073/pnas.96.14.7797
|View full text |Cite
|
Sign up to set email alerts
|

Lovastatin-mediated G 1 arrest is through inhibition of the proteasome, independent of hydroxymethyl glutaryl-CoA reductase

Abstract: In this paper we present the finding that lovastatin arrests cells by inhibiting the proteasome, which results in the accumulation of p21 and p27, leading to G 1 arrest. Lovastatin is an inhibitor of hydroxymethyl glutaryl (HMG)-CoA reductase, the rate-limiting enzyme in cholesterol synthesis. Previously, we reported that lovastatin can be used to arrest cultured cells in the G 1 phase of the cell cycle, resulting in the stabilization of the cyclin-dependent kinase inhibitors (CKIs) p21 and p27. In this report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
239
2
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 334 publications
(253 citation statements)
references
References 37 publications
10
239
2
2
Order By: Relevance
“…A recent study has shown that statins cause intracellular accumulation of A␤ via a non-steroidal isoprenoid-dependent mechanism (67). In our study, however, we added mevalonate to avoid toxicity due to inhibition of these non-steroidal pathways (51,52,54).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A recent study has shown that statins cause intracellular accumulation of A␤ via a non-steroidal isoprenoid-dependent mechanism (67). In our study, however, we added mevalonate to avoid toxicity due to inhibition of these non-steroidal pathways (51,52,54).…”
Section: Discussionmentioning
confidence: 95%
“…De novo cholesterol synthesis was inhibited by lovastatin, an inhibitor of HMG-CoA reductase. A basic level of mevalonate was maintained by adding mevalonate to the cell culture media to avoid toxicity due to inhibition of non-steroidal pathways (51,52). Plasma membrane cholesterol was extracted by methyl-␤-cyclodextrin.…”
Section: Methodsmentioning
confidence: 99%
“…First, de novo synthesis of cholesterol was inhibited by lovastatin or simvastatin. Biochemical pathways for nonsteroidal products were allowed to proceed by supplementing cells with mevalonate in the culture medium (33,34). Second, plasma membrane cholesterol was extracted by CDX, which is very efficient in selectively and rapidly extracting cholesterol from the plasma membrane (35).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that lovastatin leads to G1 arrest by inhibition of the proteosome and subsequent increase in p21 and p27 levels (Gray-Bablin et al, 1997; Rao et al, 1998Rao et al, , 1999. Cells were treated with escalating doses of lovastatin and cell cycle distribution assessed by flow cytometry (Figure 4a).…”
Section: Mdah-2774 T1 Clones Are Resistant To Lovastatinmediated G1 Amentioning
confidence: 99%